Le forme metriche nella 'Vita nova' (Quaderni di Gargnano, 2022)
This article discusses some aspects of Dante's Vita nova which are related to metrical or formal matters and that have bearing upon the prose commentary. It first reviews the role of deviations from the standard, considered on the one hand in the contemporary panorama and on the other hand with regard to the narrative context. Secondly, it analyses the Vita nova's rather sparing use of specifically metrical terminology. Finally, it explores the variable relationships between Dante's logical and thematic segmenting of lyric content in his divisioni, and the corresponding internal structures of the different metrical forms that he employed.Il contributo prende in esame alcuni aspetti del prosimetro giovanile dantesco legati alla dimensione metrico-formale che entrano in relazione con la prosa di autocommento. La prima questione affrontata è quella del ruolo dell'anomalia, da un lato rispetto al panorama coevo e dall'altro nel contesto narrativo. Viene poi analizzato l'uso dantesco (qui assai parco) della terminologia specifica della metrica. Infine, si investiga la relazione tra le partizioni logico-tematiche individuate dalle divisioni dantesche e le articolazioni interne delle diverse forme metriche utilizzate.
Keywords: Vita nova; aspetti metrico-formali; prosa di autocommento; lyric form and metre; self-commentary in prose